(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The experiment was conducted at the Bangladesh Rice Research Institute Farm, Gazipur in Aman season to determine the optimum time of planting and to find out the genotypes having high yield potential. Fine rice genotypes Basmati PNR, Basmati 370, Basmati 375, and Basmati-D were transplanted from 22 July and continued upto 7 October at an interval of 15 days both in 1999 and 2000. Thirty-day old seedlings were transplanted at a spacing of 20 cm x 15 cm. The tallest plant was found in the early-planted crop at maturity. Crop planted from 7 August to 7 September gave more number of tillers per m2, panicles per m2 and grains per panicle which resulted in higher grain yield. Compared to the 22 August planting, grain yield decreased by 11, 10, 10, 26, and 61 percent, respectively, when the crop was planted on 22 July, 7 August, 7 September, 22 September, and 7 October. The growth duration of the genotypes decreased with the advancement of planting date. Among the genotypes, Basmati PNR gave maximum grain yield followed by Basmati-D due to more number of panicles and lower percentage of spikelet sterility. The lower grain yield was found in Basmati 370 irrespective of planting date due to lower number of panicles and high percentage of spikelet sterility. The Basmati PNR matured 5-12 days earlier than the rest of the test genotypes. Thus, fine rice Basmati PNR and Basmati-D were most suitable to obtain higher grain yield when planted within 17-21 August. Key Words: Basmati rice, time of planting, Aman season. DOI: 10.3329/bjar.v34i3.3962 Bangladesh J. Agril. Res. 34(3) : 373-384, September 2009